The Pathophysiological Roles of Regulatory T Cells in the Early Phase of Systemic Sclerosis - Kobayashi, Satomi; Nagafuchi, Yasuo; Shoda, Hirofumi; Fujio, Keishi (Frontiers in Immunology, 2022)
Systemic sclerosis (SSc) is an autoimmune disease that is characterized by vascular damage and fibrosis. Both clinical manifestations and immunological disturbances are diverse according to the disease duration. Particularly, changes in immunological processes are prominent in the early phase of SSc. The orchestration of several subsets of immune cells promotes autoimmune responses and inflammation, and eventually stimulates pro-fibrotic processes. Many reports have indicated that CD4+ T cells play pivotal roles in pathogenesis in the early phase of SSc. In particular, the pathogenic roles of regulatory T (Treg) cells have been investigated. Although the results were controversial, recent reports suggested an increase of Treg cells in the early phase of SSc patients. Treg cells secrete transforming growth factor-β (TGF-β), which promotes myofibroblast activation and fibrosis. In addition, the dysfunction of Treg cells in the early phase of SSc was reported, which results in the development of autoimmunity and inflammation. Notably, Treg cells have the plasticity to convert to T-helper17 (Th17) cells under pro-inflammatory conditions. Th17 cells secrete IL-17A, which could also promote myofibroblast transformation and fibrosis and contributes to vasculopathy, although the issue is still controversial. Our recent transcriptomic comparison between the early and late phases of SSc revealed a clear difference of gene expression patterns only in Treg cells. The gene signature of an activated Treg cell subpopulation was expanded in the early phase of SSc and the oxidative phosphorylation pathway was enhanced, which can promote Th17 differentiation. And this result was accompanied by the increase in Th17 cells frequency. Therefore, an imbalance between Treg and Th17 cells could also have an important role in the pathogenesis of the early phase of SSc. In this review, we outlined the roles of Treg cells in the early phase of SSc, summarizing the data of both human and mouse models. The contributions of Treg cells to autoimmunity, vasculopathy, and fibrosis were revealed, based on the dysfunction and imbalance of Treg cells. We also referred to the potential development in treatment strategies in SSc.